Answer:
x = 3
Explanation:
![\left \{ {{6x-5y=8} \atop {2x+9y=24}} \right.](https://img.qammunity.org/2020/formulas/mathematics/middle-school/8grjivexxgfet174skuv4e2tg7w1e9xdz5.png)
I'm going to use the method of elimination by multiplying the second equation by -3:
![\left \{ {{6x-5y=8} \atop {-6x-27y=-72}} \right.](https://img.qammunity.org/2020/formulas/mathematics/middle-school/n80lrehj66dw08u7mlogajbwny0oyidqgq.png)
Then I can eliminate x:
-32y = -64
To solve for y, I'd simply divide:
y = 2
Because I now have y = 2, I'll just plug in 2:
6x - 5(2) = 8
6x - 10 = 8
6x = 18
x = 3
Hopefully I helped :)